2011
DOI: 10.1007/s10544-011-9529-3
|View full text |Cite
|
Sign up to set email alerts
|

A suction-type microfluidic immunosensing chip for rapid detection of the dengue virus

Abstract: The enzyme-linked immunosorbent assay (ELISA) is widely used in medical diagnostics. In order to reduce the diagnosis time and to lower the consumption of sample/reagents in an ELISA assay, a suction-type, automatic, pneumatically-driven microfluidic chip has been designed and fabricated in this study. The microfluidic chip integrates a multi-functional micro-transport/mixing unit, for transporting metering and mixing of samples and reagents in order to automatically perform the entire ELISA protocol. A new su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Using the same concept, Weng et al, 2011, designed a PEM-coated microfluidic platform for identifying dengue virus (DV) using ELISA [18]. The focus of this work was on the design of a device that allows for sample transport and mixing capabilities integrated into a single unit to reduce the time commonly required in conventional ELISA.…”
Section: Enzymatic Biochipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same concept, Weng et al, 2011, designed a PEM-coated microfluidic platform for identifying dengue virus (DV) using ELISA [18]. The focus of this work was on the design of a device that allows for sample transport and mixing capabilities integrated into a single unit to reduce the time commonly required in conventional ELISA.…”
Section: Enzymatic Biochipsmentioning
confidence: 99%
“…However, the stability and efficiency are improved by the use of PEMs on the channel surfaces. Weng et al, 2011, reported that the PEM/PDMS microfluidic system reduces the time required for surface modification from 24 h [17] to 2 h [18]. The PAA and PEI layers (6 nm total thicknesses) were cross-linked with amide bonds by exposing them to glutaraldehyde.…”
Section: Enzymatic Biochipsmentioning
confidence: 99%
“…Others have designed a microfluidic platform with LbL coatings for identifying the dengue virus through an enzyme-linked immunosorbent assay (ELISA) approach. The results have indicated that LbL coatings on channel surfaces improve their stability and efficiency, reducing surface modification time 12-fold 48 . Alternatively, LbL-modified microfluidic systems have been used to control the flow or flow constituents within the device.…”
Section: Introductionmentioning
confidence: 96%
“…Due to their small scale, microdevices have many practical advantages such as large specific volume, very low reagent consumption, and short diffusion length. Several developmental advances have been realized in miniaturization of capillary electrophoresisbased immunoassays (Ou et al 1999;Roper et al 2003;Herr et al 2005;Chen and Zhang 2008;Hui and Ma 2011) and microchip-based ELISA (Rossier and Girault 2001;Murakami et al 2004;Kang and Park 2005;Zhao et al 2008;Weng et al 2011;Schrott et al 2011). The capillary electrophoresis-based immunoassays utilize an electric field to separate the antigenantibody complex from the rest of the molecules in the assay solutions.…”
Section: Introductionmentioning
confidence: 99%